Homosexualité et droits à l'égalité dans les Chartes canadienne et québécoise - Duplé, Nicole (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
To what extent may a person be discriminated against within the purview of a federal or Quebec law because of his or her homosexuality ? The author attempts to answer this question in the light of the Canadian Charter of Rights and Freedoms and the Quebec Charter of Human Rights and Freedoms. Those two documents make up two distinct sources against discrimination. The question as to whether section 15 of the Canadian Charter prohibits distinctions based upon homosexuality is examined in the first part of the article. The second part focuses on the nature and scope of the right of the homosexual person to complete equality under the Quebec Charter.